Tingkat Pengetahuan tentang Kanker Payudara dan Perilaku SADARI pada Mahasiswi Prodi Kedokteran Fakultas Kedokteran Universitas Mulawarman: Level of Knowledge about Breast Cancer and BSE Behaviours in Students of Medical Study Program, Faculty of Medicine, University of Mulawarman - Enggarita Widyahapsari; Hadi Irawiraman; Endang Sawitri (Jurnal Sains dan Kesehatan, 2021)
Breast cancer is the most type of cancer that affects women in worldwide. The high mortality rate due to breast cancer is caused by the large number of cancer patients who have just arrived at an advanced stage. Breast self-examination (BSE) is an effort to detect breast cancer as early as possible so that it can reduce morbidity and mortality, in which predisposing factors including the level of knowledge can affect a person's willingness to perform breast cancer screening. This study aimed to determine the level of knowledge about breast cancer and BSE behaviour in students of Medical, Faculty of Medicine, Mulawarman University Samarinda. This research was a descriptive study with a cross-sectional approach. Data sources were primary. Primary data was obtained by using a questionnaire instrument that was filled out via google form. Secondary data was obtained from the data archive of the number of female students kept by the Academic and Student Affairs subdivision. The research sample were 111 students of the Medical, 4th year class (37,8%), 3rd year class (35,1%), and 2nd year class (27%), Faculty of Medicine, Mulawarman University Samarinda. The result showed that the level of knowledge about the breast cancer in the low category was 3 (2.7%), the medium category was 44 (39.6%), and the high category was 64 (57.7%). The poor BSE behaviour was in 13 (11.7%), good enough behaviour was 70 (63.1%) and excellent behaviour was 28 (25.2%). The conclusion is most of the medical students already had good knowledge about breast cancer and good enough BSE behaviour.